Coronavirus in Colombia: Stigma and quarantine (2020)
This study describes a brief history of the spread of coronavirus, listing the disease’s main characteristics. The decisions made by the Colombian government are presented, as there have been progressively more cases of infection, death and recovery, in addition to the stigmatisation that the medical personnel who are treating COVID-19 patients have experienced from some people in Colombia. Issues related to intra-family and domestic partner violence occurring in Colombia because of the quarantine processes are also addressed. Early stress studies in general population and medical professionals. The lines of work being implemented by the Colombian Association of Psychology (COLPSIC, for its Spanish acronym) for psychological help towards the affected population are described. Finally, psychological intervention initiatives that are important to implement for mental well-being are discussed.